Triethylene glycol ammonium phosphate flame retardant, green flame-retardant finishing liquid and preparation method and application of triethylene glycol ammonium phosphate flame retardant and green flame-retardant finishing liquid
By preparing triethylene glycol amine phosphate flame retardant and green flame retardant finishing solution, the problem of insufficient flame retardant performance of suede fabrics is solved, and an efficient, non-toxic and environmentally friendly flame retardant effect is achieved, meeting the environmental protection requirements of modern society.
Patent Information
- Application Number
- CN202510220815.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-27
AI Technical Summary
The flame retardant properties of echoed suede fabrics are insufficient. Traditional halogen-containing flame retardants release toxic gases when burning, which cannot meet the requirements of modern society for green and environmental protection.
A flame retardant with triethylene glycol amine phosphate salt and a green flame retardant finishing solution were used to form a flame retardant through the condensation reaction principle, and combined with 3-aminopropyltriethoxysilane to prepare a flame retardant with high efficiency, non-toxic and environmentally friendly flame retardant.
During the combustion process, the flame retardant can quickly form charcoal, form a dense carbon layer, insulate the inside of the material from contact with air, generate non-toxic or low-toxic gases, improve the carbon-forming properties and high-temperature resistance of the fiber material, and meet environmental protection requirements.
Smart Images

Figure CN119708047A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile fabrics, and in particular to a triethylene glycol amine phosphate flame retardant and a green flame retardant finishing liquid, and a preparation method and application thereof. Background Art
[0002] Suede-like fabrics occupy an important position in many fields with their unique texture and performance. It has a soft and delicate touch similar to natural suede, and has good warmth retention and moisture absorption, which makes it popular in industries such as clothing, home decoration, and automotive interiors. In terms of production technology, suede-like fabrics are usually made of polyester microfibers and other raw materials, and are made into base fabrics by needle punching, spunlace or weaving. Subsequently, after a series of complex post-processing processes such as dyeing, sanding, and shaping, products that meet market demand can finally be presented. However, although suede-like fabrics perform well in appearance and some performance, it has a key problem-serious lack of flame retardancy. In actual application scenarios, the lack of flame retardancy may cause a series of safety hazards.
[0003] In order to solve the problem of insufficient flame retardancy, the traditional method is to add halogen-containing flame retardants. Halogen-containing flame retardants can improve the flame retardancy of materials to a certain extent. However, this method brings more serious negative effects. During the combustion process, halogen-containing flame retardants will release a large amount of toxic gases, of which hydrogen halide is one of the main components. These toxic gases are harmful to human health in many ways.
[0004] With the development of society and people's increasing awareness of environmental protection, the environmental protection requirements for products are getting higher and higher. Traditional halogen-containing flame retardants obviously cannot meet the requirements of modern society for green environmental protection. Consumers are more inclined to choose products that have good performance and are friendly to the environment and human health. Therefore, in the field of suede-like fabrics, it is urgent to develop a new type of flame retardant with high-efficiency flame retardant performance, non-toxicity, and environmental protection. Summary of the invention
[0005] The purpose of the present invention is to provide a triethylene glycol amine phosphate flame retardant and a green flame retardant finishing liquid and a preparation method and application thereof in order to overcome the deficiencies of the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a triethylene glycol amine phosphate flame retardant, comprising the following steps: 1) Triethylene glycol and phosphoric acid are mixed and reacted to obtain a viscous solution; 2) Dropping urea solution into the viscous solution to react, thereby obtaining triethylene glycol amine phosphate flame retardant.
[0007] Preferably, the molar ratio of triethylene glycol, phosphoric acid and urea in the urea solution is 1:1.8-2.2:3-5; the molar volume ratio of urea to water in the urea solution is 1.5×10 -2 ~2.5×10 -2 mol:1mL.
[0008] Preferably, the reaction temperature in step 1) is 135-145° C., and the reaction time is 2.5-3.5 h; the reaction temperature in step 2) is 165-175° C., and the reaction time is 1.8-2.2 h.
[0009] The present invention also provides the triethylene glycol amine phosphate flame retardant prepared by the preparation method of the triethylene glycol amine phosphate flame retardant.
[0010] The present invention also provides a method for preparing a green flame retardant finishing liquid using the triethylene glycol amine phosphate flame retardant, comprising the following steps: 3-aminopropyltriethoxysilane and water are mixed to obtain a colloidal solution; an aqueous solution of triethylene glycol amine phosphate is dripped into the colloidal solution to obtain a green flame retardant finishing liquid.
[0011] Preferably, in the colloidal solution, the molar volume ratio of 3-aminopropyltriethoxysilane to water is 4×10 -4 ~5×10 -4 mol: 1mL; in the aqueous solution of triethylene glycol amine phosphate, the molar volume ratio of triethylene glycol amine phosphate and water is 9×10 -4 ~1.5×10 -3 mol:1mL.
[0012] Preferably, the volume ratio of the aqueous solution of triethylene glycol amine phosphate to the colloidal solution is 2.5-3.5:1; and the mixing time is ≥12h.
[0013] The present invention also provides a green flame retardant finishing liquid prepared by the method for preparing a green flame retardant finishing liquid using the triethylene glycol amine phosphate flame retardant.
[0014] The present invention also provides the use of the green flame retardant finishing liquid in suede-like fabrics, wherein the suede-like fabrics are immersed in the green flame retardant finishing liquid and then sequentially cured, washed and dried to obtain flame retardant suede-like fabrics; The dipping time is 5 to 8 minutes, the curing temperature is 145 to 155° C., the curing time is 10 to 15 minutes, the drying temperature is 75 to 85° C., and the drying time is 3 to 4 hours.
[0015] Preferably, before impregnation, the green flame retardant finishing liquid is stirred at 75-85°C for ≥3h; after impregnation, the liquid loading rate of the fabric is controlled to be 125-135% before curing.
[0016] The beneficial effects of the present invention include the following: 1) In the present invention, triethylene glycol, phosphoric acid and urea utilize the condensation reaction principle to form a triethylene glycol phosphate amine salt flame retardant. The structure of the flame retardant also contains rich nitrogen and phosphorus elements, so that the flame retardant can quickly char during the combustion process to form a dense carbon layer, thereby achieving the purpose of isolating the inside of the material from contact with the air; during high-temperature combustion and degradation, non-toxic, difficult to flammable gas or smoke can be generated to reduce the oxygen concentration, and the residual carbon containing phosphorus elements generates an expanded carbon layer due to the release of gas, thereby isolating the heat and flammable gas generated during the combustion process. The simultaneous introduction of nitrogen and phosphorus can play a good synergistic flame retardant effect.
[0017] 2) In the present invention, 3-aminopropyl triethoxysilane is added to the flame retardant finishing liquid, and the compound use with triethylene glycol ammonium phosphate has good flame retardant synergistic effect, which can improve the carbonization of fiber materials. First, the siloxane structure is not easy to thermally decompose at high temperature, and can form a physical cross-linking network with polyester fiber during the melting process, which is beneficial to increase the thermal decomposition temperature of the fiber and enhance the high temperature resistance; secondly, the siloxane structure is thermally decomposed at high temperature to generate inorganic silicon, which is compounded with the carbon layer on the surface of the material to form a continuous and dense covering layer, which has the effect of heat insulation and oxygen isolation, and can inhibit the combustion process of polyester fiber. At the same time, the covering layer can inhibit the volatilization of smoke, improve smoke suppression and anti-melting droplet properties.
[0018] 3) The impregnation method of the present invention is an effective process for applying green flame retardant finishing liquid to suede-like fabrics. During the impregnation process, the flame retardant finishing liquid fully contacts the fiber and penetrates into the fiber. At the same time, the flame retardant molecules are adsorbed on the fiber surface and inside and can be firmly attached to the fiber. After impregnation and drying, the fiber is subjected to high temperature treatment to thermally cure the flame retardant on the fiber. This step not only enhances the bonding force between the flame retardant and the fiber, but also makes it more stable; at the same time, the high temperature treatment can also cause the flame retardant molecules to undergo further chemical reactions on the fiber to form a more stable structure, thereby improving the durability and anti-aging properties of the flame retardant.
[0019] 4) The green flame retardant finishing liquid of the present invention contains nitrogen, phosphorus and silicon flame retardants, which conform to the concept of environmental protection. On the one hand, it does not contain toxic halogens, mainly produces non-toxic or low-toxic gases when burned, and the decomposition products are relatively safe. In addition, no formaldehyde is produced during the application process, avoiding the direct harm of formaldehyde to the human body and ensuring human health and environmental safety. On the other hand, nitrogen, phosphorus and silicon elements are abundant in nature, the raw materials are widely available and relatively cheap, the production process is relatively environmentally friendly, and less three wastes are produced, which has significant practical value and broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1It is a schematic diagram of the effect of applying the green flame retardant finishing liquid of the present invention to suede-like fabric; Figure 2 is the Fourier transform infrared spectrum of the triethylene glycol amine phosphate flame retardant of Example 1; Figure 3 The limiting oxygen index test results of the flame retardant suede-like fabrics prepared in Examples 1 to 3 and Comparative Examples 1 to 3; Figure 4 The heat release peak and total heat release of the flame retardant suede-like fabrics prepared in Examples 1 to 3 and Comparative Examples 1 to 3. DETAILED DESCRIPTION
[0021] The present invention provides a method for preparing a triethylene glycol amine phosphate flame retardant, comprising the following steps: 1) Triethylene glycol and phosphoric acid are mixed and reacted to obtain a viscous solution; 2) Dropping urea solution into the viscous solution to react, thereby obtaining triethylene glycol amine phosphate flame retardant.
[0022] In the present invention, the molar ratio of triethylene glycol, phosphoric acid and urea in the urea solution is preferably 1:1.8-2.2:3-5, more preferably 1:1.9-2.1:3.5-4.5, and more preferably 1:2:4; in the urea solution, the molar volume ratio of urea to water is preferably 1.5×10 -2 ~2.5×10 -2 mol: 1mL, more preferably 1.7×10 -2 ~2.3×10 -2 mol: 1mL, more preferably 2×10 -2 mol:1mL.
[0023] In the present invention, the reaction temperature in step 1) is preferably 135-145°C, more preferably 137-142°C, more preferably 140°C, and the reaction time is preferably 2.5-3.5h, more preferably 2.8-3.2h, more preferably 3h; the reaction temperature in step 2) is preferably 165-175°C, more preferably 168-172°C, more preferably 170°C, and the reaction time is preferably 1.8-2.2h, more preferably 2h.
[0024] In the present invention, the mixing in step 1) is preferably performed by dropping phosphoric acid into triethylene glycol; magnetic stirring is performed during the mixing and reaction, and the viscous solution is a brown viscous solution.
[0025] In the present invention, the synthetic route for preparing triethylene glycol phosphate amine salt from triethylene glycol, phosphoric acid and urea is:
[0026] The present invention also provides the triethylene glycol amine phosphate flame retardant prepared by the preparation method of the triethylene glycol amine phosphate flame retardant.
[0027] The present invention also provides a method for preparing a green flame retardant finishing liquid using the triethylene glycol amine phosphate flame retardant, comprising the following steps: 3-aminopropyltriethoxysilane and water are mixed to obtain a colloidal solution; an aqueous solution of triethylene glycol amine phosphate is dripped into the colloidal solution to obtain a green flame retardant finishing liquid.
[0028] In the present invention, the molar volume ratio of 3-aminopropyltriethoxysilane to water in the colloidal solution is preferably 4×10 -4 ~5×10 -4 mol: 1mL, more preferably 4.3×10 -4 ~4.7×10 -4 mol: 1mL, more preferably 4.5×10 -4 mol: 1mL; in the aqueous solution of triethylene glycol amine phosphate, the molar volume ratio of triethylene glycol amine phosphate and water is preferably 9×10 -4 ~1.5×10 -3 mol: 1mL, more preferably 1×10 -3 ~1.3×10 -3 mol: 1mL, more preferably 1.1×10 -3 ~1.2×10 -3 mol:1mL.
[0029] In the present invention, the volume ratio of the aqueous solution of triethylene glycol amine phosphate to the colloidal solution is preferably 2.5-3.5:1, more preferably 2.8-3.2:1, and more preferably 3:1; the mixing time is preferably ≥12h, and more preferably ≥14h.
[0030] The present invention also provides a green flame retardant finishing liquid prepared by the method for preparing a green flame retardant finishing liquid using the triethylene glycol amine phosphate flame retardant.
[0031] The invention also provides application of the green flame retardant finishing liquid in suede-like fabrics. The suede-like fabrics are immersed in the green flame retardant finishing liquid and then cured, washed and dried in sequence to obtain flame retardant suede-like fabrics.
[0032] In the present invention, the impregnation time is preferably 5 to 8 minutes, more preferably 6 to 7 minutes, the curing temperature is preferably 145 to 155°C, more preferably 147 to 152°C, more preferably 149 to 150°C, the curing time is preferably 10 to 15 minutes, more preferably 11 to 14 minutes, more preferably 12 to 13 minutes, the drying temperature is preferably 75 to 85°C, more preferably 78 to 82°C, more preferably 80°C, and the drying time is preferably 3 to 4 hours, more preferably 3.2 to 3.7 hours, more preferably 3.5 hours.
[0033] In the present invention, before impregnation, the green flame retardant finishing liquid is preferably stirred at 75-85°C, more preferably at 78-82°C, more preferably at 80°C, and the stirring time is preferably ≥3h, more preferably ≥4h; after impregnation, the liquid loading rate of the fabric is controlled to be 125-135% before curing, more preferably 128-132%, more preferably 130%.
[0034] The schematic diagram of the effect of the green flame retardant finishing liquid of the present invention on the suede-like fabric is as follows: Figure 1 shown.
[0035] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0036] Example 1
[0037] 15g (0.1mol) of triethylene glycol was added dropwise to a 250mL round-bottom flask, and then 19.6g (0.2mol) of phosphoric acid crystals were added. The flask was placed in a constant temperature oil bath, and heated and stirred at 140°C for 3h to obtain a brown viscous solution. 24g (0.4mol) of urea was dissolved in 20mL of deionized water, and added dropwise to the brown viscous solution at a rate of 10mL / min, and the temperature was raised to 170°C. The solution was stirred at a speed of 500r / min for 2h in a constant temperature oil bath. After the reaction was completed, it was cooled to room temperature to obtain a brown viscous product (triethylene glycol amine phosphate flame retardant).
[0038] 3-Aminopropyltriethoxysilane was added to deionized water (the molar volume ratio of 3-aminopropyltriethoxysilane to deionized water was 4.5×10 -4 mol: 1mL) and stirred magnetically for 12h to obtain 60mL of colorless and transparent colloidal solution; triethylene glycol amine phosphate was dissolved in deionized water (the molar volume ratio of triethylene glycol amine phosphate to deionized water was 1.1×10 -3 mol: 1mL) to obtain 200mL of triethylene glycol amine phosphate solution, and the colloidal solution was dropped into the triethylene glycol amine phosphate solution to obtain a green flame retardant finishing liquid.
[0039] The green flame retardant finishing liquid was heated to 80°C and stirred at a speed of 500r / min for 3h. A 10cm×10cm suede-like fabric was placed in the finishing liquid and fully immersed for 5min. The suede-like fabric was taken out and the liquid loading rate was controlled to be 130%; then the suede-like fabric was placed in an oven and cured at 150°C for 10min. The suede-like fabric was then washed in clean water and dried in a drying machine at a temperature of 80°C for 3.5h to obtain a flame retardant suede-like fabric.
[0040] The Fourier transform infrared spectrum of the triethylene glycol amine phosphate flame retardant of Example 1 is as follows: Figure 2 As shown by Figure 2 It can be seen that the absorption peak of triethylene glycol amine phosphate is located at 3214 cm -1 and 2893cm -1 , respectively, belonging to NH in the structure 4 + ions and CH 2 Chemical vibration absorption peak of bond; at 1178cm -1 An additional absorption peak was detected at 1093 cm -1 The stretching vibration of the PO bond was observed at 140°C. These all prove the accuracy of the chemical structure of the triethylene glycol amine phosphate flame retardant, and further prove the successful synthesis of the flame retardant.
[0041] Example 2
[0042] 30g (0.2mol) of triethylene glycol was added dropwise to a 250mL round-bottom flask, and then 39.2g (0.4mol) of phosphoric acid crystals were added. The flask was placed in a constant temperature oil bath, heated and stirred at 140°C for 3h to obtain a brown viscous solution. 48g (0.8mol) of urea was dissolved in 40mL of deionized water, and added dropwise to the brown viscous solution at a rate of 10mL / min, and the temperature was raised to 170°C. The solution was stirred at a speed of 500r / min for 2h in a constant temperature oil bath. After the reaction was completed, it was cooled to room temperature to obtain a brown viscous product (triethylene glycol amine phosphate flame retardant).
[0043] 3-Aminopropyltriethoxysilane was added to deionized water (the molar volume ratio of 3-aminopropyltriethoxysilane to deionized water was 4.7×10 -4 mol: 1mL) and stirred magnetically for 13h to obtain 120mL of colorless and transparent colloidal solution; triethylene glycol amine phosphate was dissolved in deionized water (the molar volume ratio of triethylene glycol amine phosphate to deionized water was 1×10 -3 mol: 1mL) to obtain 400mL of triethylene glycol amine phosphate solution, and the colloidal solution was dropped into the triethylene glycol amine phosphate solution to obtain a green flame retardant finishing liquid.
[0044] The green flame retardant finishing liquid was heated to 80°C and stirred at a speed of 500r / min for 3h. A 10cm×10cm suede-like fabric was placed in the finishing liquid and fully immersed for 5min. The suede-like fabric was taken out and the liquid loading rate was controlled to be 130%; then the suede-like fabric was placed in a vacuum oven and cured at 150°C for 10min. The suede-like fabric was then washed in clean water and dried in a drying machine at a temperature of 80°C for 3h to obtain a flame retardant suede-like fabric.
[0045] Example 3
[0046] 45g (0.3mol) of triethylene glycol was added dropwise to a 250mL round-bottom flask, and then 58.8g (0.6mol) of phosphoric acid crystals were added. The flask was placed in a constant temperature oil bath, heated and stirred at 140°C for 3h to obtain a brown viscous solution. 72g (1.2mol) of urea was dissolved in 60mL of deionized water, and added dropwise to the brown viscous solution at a rate of 10mL / min, and the temperature was raised to 170°C. The solution was stirred at a speed of 500r / min for 2h in a constant temperature oil bath. After the reaction was completed, it was cooled to room temperature to obtain a brown viscous product (triethylene glycol amine phosphate flame retardant).
[0047] 3-Aminopropyltriethoxysilane was added to deionized water (the molar volume ratio of 3-aminopropyltriethoxysilane to deionized water was 4.3×10 -4 mol: 1mL) and stirred magnetically for 14h to obtain 120mL of colorless and transparent colloidal solution; triethylene glycol amine phosphate was dissolved in deionized water (the molar volume ratio of triethylene glycol amine phosphate to deionized water was 1.4×10 -3 mol: 1mL) to obtain 400mL of triethylene glycol amine phosphate solution, and the colloidal solution was dropped into the triethylene glycol amine phosphate solution to obtain a green flame retardant finishing liquid.
[0048] The green flame retardant finishing liquid was heated to 80°C and stirred at a speed of 500r / min for 3h. A 10cm×10cm suede-like fabric was placed in the finishing liquid and fully immersed for 5min. The suede-like fabric was taken out and the liquid loading rate was controlled to be 130%; then the suede-like fabric was placed in a vacuum oven and cured at 150°C for 10min. The suede-like fabric was then washed in clean water and dried in a dryer at 80°C for 4h to obtain a flame retardant suede-like fabric.
[0049] Comparative Example 1 The molar volume ratio of triethylene glycol amine phosphate and deionized water in Example 1 was changed to 1.4×10 -4 mol: 1mL, other conditions are the same as in Example 1.
[0050] Comparative Example 2 The molar volume ratio of triethylene glycol phosphate amine salt and deionized water in Example 1 was changed to 3.2×10 -4 mol: 1mL, other conditions are the same as in Example 1.
[0051] Comparative Example 3 The molar volume ratio of triethylene glycol amine phosphate and deionized water in Example 1 was changed to 6.6×10 -4 mol: 1mL, other conditions are the same as in Example 1.
[0052] The flame retardant suede-like fabrics of Examples 1 to 3 and Comparative Examples 1 to 3 were tested for performance. The flame retardant suede-like fabrics prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested using a limiting oxygen index tester and a cone calorimeter to observe changes in the limiting oxygen index value, heat release rate, and total heat release of the fabrics.
[0053] The limiting oxygen index test results of the flame retardant suede-like fabrics prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are as follows: Figure 3 As shown, the results show that the limiting oxygen index value of the suede-like fabric treated with the flame retardant finishing liquid of the present invention is about 35, indicating that the flame retardant finishing liquid has a good flame retardant effect on the fabric. With the increase of the number of washing times, the flame retardancy of the fabric gradually decreases.
[0054] The heat release peak and total heat release of the flame retardant suede-like fabrics prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are as follows: Figure 4 As shown. The peak heat release and total heat release are important indicators for judging the flame retardant properties of fabrics. The peak heat release reflects the severity of the fire and the rapidity of energy release during combustion. Fabrics with good flame retardant properties have suppressed combustion reactions and low peak heat release; conversely, they are high. The total heat release reflects the total amount of energy released during the entire combustion process. Flame retardant fabrics have reduced total heat release due to the flame retardant or their own structure that limits the decomposition and combustion of combustible materials. Fabrics that do not have flame retardant properties have high total heat release. Figure 4 It can be seen that the embodiments and comparative examples basically show a positive correlation trend between the peak heat release and the total heat release. The peak heat release and total heat release of the flame-retardant suede-like fabrics prepared in Examples 1 to 3 prove that the fabrics have good flame retardant properties. From the bar graph, it can be seen that with the increase in the concentration of triethylene glycol amine phosphate, the peak heat release and total heat release of the fabric gradually decrease, indicating that the concentration of the flame retardant has a significant effect on the flame retardant properties. When the concentration increases, the peak heat release decreases, because the flame retardant decomposes to produce non-combustible gases and forms a barrier layer to slow down combustion; the total heat release decreases, and the consumption of combustible components is reduced by taking away heat and promoting carbonization. In addition, the peak heat release and total heat release of the fabric in the comparative example are higher than the peak heat release and total heat release of the fabric in Examples 1 to 3, indicating that the flame retardant properties of the fabric in the embodiment are better than those of the fabric in the comparative example.
[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a triethylene glycol amine phosphate flame retardant, characterized in that: The following steps are included: 1) Triethylene glycol and phosphoric acid are mixed and reacted to obtain a viscous solution; 2) Dropping urea solution into the viscous solution to react, thereby obtaining triethylene glycol amine phosphate flame retardant.
2. The method for preparing the triethylene glycol amine phosphate flame retardant according to claim 1, characterized in that: The molar ratio of urea in triethylene glycol, phosphoric acid and urea solution is 1:1.8~2.2:3~5; in urea solution, the molar volume ratio of urea to water is 1.5×10 -2 ~2.5×10 -2 mol:1mL.
3. The method for preparing the triethylene glycol amine phosphate flame retardant according to claim 1 or 2, characterized in that: The reaction temperature of step 1) is 135-145°C, and the reaction time is 2.5-3.5h; the reaction temperature of step 2) is 165-175°C, and the reaction time is 1.8-2.2h.
4. The triethylene glycol amine phosphate flame retardant prepared by the preparation method of the triethylene glycol amine phosphate flame retardant according to any one of claims 1 to 3.
5. The method for preparing green flame retardant finishing liquid using triethylene glycol amine phosphate flame retardant according to claim 4, characterized in that: The following steps are included: 3-aminopropyltriethoxysilane and water are mixed to obtain a colloidal solution; an aqueous solution of triethylene glycol amine phosphate is dripped into the colloidal solution to obtain a green flame retardant finishing liquid.
6. The method for preparing a green flame retardant finishing liquid using the triethylene glycol amine phosphate flame retardant according to claim 5, characterized in that: In the colloidal solution, the molar volume ratio of 3-aminopropyltriethoxysilane to water is 4×10 -4 ~5×10 -4 mol: 1mL; in the aqueous solution of triethylene glycol amine phosphate, the molar volume ratio of triethylene glycol amine phosphate and water is 9×10 -4 ~1.5×10 - 3 mol:1mL.
7. The method for preparing a green flame retardant finishing liquid using the triethylene glycol amine phosphate flame retardant according to claim 5 or 6, characterized in that: The volume ratio of the aqueous solution of triethylene glycol amine phosphate to the colloidal solution is 2.5-3.5:1; and the mixing time is ≥12h.
8. The green flame retardant finishing liquid prepared by the method for preparing a green flame retardant finishing liquid using the triethylene glycol amine phosphate flame retardant according to any one of claims 5 to 7.
9. The use of the green flame retardant finishing liquid according to claim 8 in suede-like fabrics, characterized in that: The suede-like fabric is immersed in a green flame-retardant finishing liquid, and then cured, washed and dried in sequence to obtain a flame-retardant suede-like fabric; The dipping time is 5 to 8 minutes, the curing temperature is 145 to 155° C., the curing time is 10 to 15 minutes, the drying temperature is 75 to 85° C., and the drying time is 3 to 4 hours.
10. The use of the green flame retardant finishing liquid in suede-like fabric according to claim 9, characterized in that: Before impregnation, the green flame retardant finishing liquid is stirred at 75-85°C for ≥3h; after impregnation, the liquid loading rate of the fabric is controlled to be 125-135% before curing.
Citation Information
Patent Citations
Liquid halogen-free phosphorus-nitrogen collaboration flame retardant and preparation method thereof
CN102532599A
Preparation method of flame retarding finishing agent and flame retarding regenerated cellulose fibers
CN108018715A
B / P / N ternary synergistic flame retardant and preparation method and application thereof
CN115677754A
Flame-retardant waterborne polyurethane coating, preparation method thereof and microfiber leather
CN116814150A
Preparation method of halogen-free flexible flame-retardant cotton fabric containing nitrogen, phosphorus and silicon
CN119102103A